2018
DOI: 10.1016/j.bbmt.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cytomegalovirus Reactivation in Haploidentical Stem Cell Transplantation

Abstract: Cytomegalovirus (CMV) infection can increase the morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). Because of a higher degree of immunosuppression, haploidentical transplant recipients may be at an increased risk of viral infections, particularly CMV. We retrospectively analyzed 86 haploidentical HCT recipients at our institution to determine whether a more intensified antiviral strategy would reduce the incidence of CMV reactivation compared with a traditional antiviral prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
1
32
1
Order By: Relevance
“…Our institution reported rates of CMV viremia of 66.3% in a contemporary cohort of T‐cell–depleted HCT recipients.0 . Similarly, a 53%‐81% incidence of CMV viremia was reported in haploidentical allo‐HCT . In our study, clinically significant CMV was detected in only 1 of 30 patients (3%) who received a T‐cell–depleted or haploidentical allo‐HCT and took letermovir prophylaxis for a median of 122 days (range, 12‐270).…”
Section: Discussionsupporting
confidence: 61%
“…Our institution reported rates of CMV viremia of 66.3% in a contemporary cohort of T‐cell–depleted HCT recipients.0 . Similarly, a 53%‐81% incidence of CMV viremia was reported in haploidentical allo‐HCT . In our study, clinically significant CMV was detected in only 1 of 30 patients (3%) who received a T‐cell–depleted or haploidentical allo‐HCT and took letermovir prophylaxis for a median of 122 days (range, 12‐270).…”
Section: Discussionsupporting
confidence: 61%
“…Bone marrow suppression limits the application of prophylactic ganciclovir in allo‐HSCT. Additionally, Hammerstrom et al demonstrated that an intensified valacyclovir approach significantly lowers the incidence of CMV infection as compared to that for standard‐dose valacyclovir. Recently, the efficacy of letermovir prophylaxis has been demonstrated; it significantly lowers the risk of clinically significant CMV infection compared with that of a placebo in allo‐HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…This approach resulted in significantly lower CMV reactivation and disease rates, as well as fewer days on anti-CMV therapy in patients with CMV reactivation. Similar strategies have been adopted for use in high-risk CBT recipients at other centers [1,9,10]. We subsequently instituted a modified intensive strategy that excluded pretransplantation ganciclovir given the potential for additional side effects, logistical barriers, and cost, with unclear benefit in the context of additional aspects of the prevention strategy.…”
Section: Introductionmentioning
confidence: 99%